Sacroiliac joint dysfunction in elite rowers - Timm, K. E. (Journal of Orthopaedic & Sports Physical Therapy, 1999)
STUDY DESIGN: Cross-sectional, descriptive study. OBJECTIVES: To examine the occurrence of sacroiliac joint dysfunction (SIJD) in a group of elite rowers. BACKGROUND: Sacroiliac joint dysfunction is a common problem for elite athletes, but is largely unstudied in the medical literature. METHODS AND MEASURES: The United States Senior National Rowing Teams at the Pan American Games and the World Rowing Championships in 1995 were tested for SIJD through the standing flexion test followed by palpatory examination of anatomic landmarks. RESULTS: Sacroiliac joint dysfunction occurred in 54.1% of team members. Sacroiliac joint dysfunction was prevalent in both sweep rowers (66%) and scullers (34%). Prevalence of SIJD did not differ among the specific types of SIJD, the side of involvement, or for the handedness of sweep rowing. CONCLUSIONS: Sacroiliac joint dysfunction is an important orthopaedic problem in rowers. This information may be useful for clinicians who treat rowers and elite athletes.